The husbands [large type] - Baker, Chandler (Thorndike Press, a part of Gale, a Cengage Company, 2021)
"Nora Spangler is a successful attorney but when it comes to domestic life, she packs the lunches, schedules the doctor appointments, knows where the extra paper towel rolls are, and designs and orders the holiday cards. Her husband works hard, too... but why does it seem like she is always working so much harder? When the Spanglers go house hunting in Dynasty Ranch, an exclusive suburban neighborhood, Nora meets a group of high-powered women--a tech CEO, a neurosurgeon, an award-winning therapist, a bestselling author--with enviably supportive husbands. When she agrees to help with a resident's wrongful death case, she is pulled into the lives of the women there. She finds the air is different in Dynasty Ranch. The women aren't hanging on by a thread. But as the case unravels, Nora uncovers a plot that may explain the secret to having-it-all. One that's worth killing for. Calling to mind a Stepford Wives gender-swap, The Husbands imagines a world where the burden of the "second shift" is equally shared--and what it may take to get ther"-- Provided by publisher.